Restoration of Parity Symmetry Through Presymmetry - Matute-Carvajal, E (2011)
Presymmetry, the hidden symmetry underlying the charge and generational patterns of quarks and leptons, is utilized for repairing the left-right asymmetry of the standard model with Dirac neutrinos. It is shown that the restoration of parity is consequent with an indispensable left-right symmetric residual presymmetry. Thus, presymmetry substantiates left-right symmetry and the experimental search for the latter is the test of the former, with the nature of neutrinos as a crucial feature that can distinguish the left-right symmetry alone and its combination with presymmetry. This phenomenological implication is in accordance with the fact that Majorana neutrinos are usually demanded in the first case, but forbidden in the second. © 2011 World Scientific Publishing Company.